History, Recollection and Conjecture (Res Medica, 2014)
Imagination has to fill in the gaps (and there are many) of recorded history. Even recorded history may not be accurate, but imagination can lead one seriously astray. In researching Library Committee minutes while preparing my dissertation many years ago I remember finding that in the years 1917 -19 the business of the Library was incorporated with that of the other Committees in a conjoint Committee due to the small number of members.